2015
DOI: 10.1093/rheumatology/kev223
|View full text |Cite
|
Sign up to set email alerts
|

Renal involvement in primary Sjögren’s syndrome

Abstract: SS is a prevalent and underdiagnosed systemic disease that primarily affects epithelial tissue. It may affect renal function either as epithelial disease causing tubulointerstitial nephritis or as an immune complex-mediated glomerulopathy. These lesions may cause a variety of clinical features, both overt and occult. The epithelial disease is mediated by B and T cells, notably the Th17 subtype. We review the prevalence of renal SS, its presentation, likely pathogenesis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 61 publications
0
68
0
20
Order By: Relevance
“…Patients tend to develop renal pathoses relatively early in the disease course, with a mean diagnosis age of 41 years [19]. Recent studies suggest tubular interstitial nephritis is the most common renal disease manifestation in SS patients [20, 21], and this is characterized by renal inflammation [19, 22, 23]. Thus, our findings in NOD.B10 mice mimic the renal histopathology seen in SS patients, although further studies are needed to establish the functional consequence of this in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Patients tend to develop renal pathoses relatively early in the disease course, with a mean diagnosis age of 41 years [19]. Recent studies suggest tubular interstitial nephritis is the most common renal disease manifestation in SS patients [20, 21], and this is characterized by renal inflammation [19, 22, 23]. Thus, our findings in NOD.B10 mice mimic the renal histopathology seen in SS patients, although further studies are needed to establish the functional consequence of this in our model.…”
Section: Discussionmentioning
confidence: 99%
“…4 Some studies correlated RTA and high anti-SS A/Ro and anti-SS B/La dRTA in Primary Sjögren's Syndrome level titers as a surrogate of pSS progression. 15,16 Additionally, other studies have suggested that lymphoplasmacytic infiltrates surrounding renal tubules are associated with renal tubular defects.…”
Section: Discussionmentioning
confidence: 99%
“…3 Primary Sjögren's syndrome (pSS) mainly affects exocrine glands; nevertheless it can impair renal function via tubular and glomerular injury. 4 In adults, pSS has been identified as the leading cause of acquired dRTA. 5 The relevance of this case stands in the atypical clinical presentation of symptomatic, severe hypokalemia as the first manifestation of pSS.…”
mentioning
confidence: 99%
“…Type II proximal tubular dysfunction consists of proteinuria, aminoaciduria, glycosuria, phosphaturia, uricosuria and bicarbonaturia (Fanconi syndrome) and may lead to osteomalacia as a consequence of phosphate wasting. Type I and IV distal renal tubular acidosis is due to a complete or incomplete inadequate H+ secretion in the cortical collecting duct by the acid-secreting a-intercalated cells (30). Distal renal tubular acidosis in pSS was found to be associated with anti-Ro and La antibodies, longer disease duration, xerostomia, hypertension, higher creatinine and proteinuria, and also hypergammaglobulinaemia (31).…”
Section: N Renal Involvementmentioning
confidence: 99%